TANTANGAN GEREJA DALAM MENGATASI KENAKALAN REMAJA KRISTEN DI GABK BUKIT MORIA MANGAIS - Pira Satria Sitoki; Junni Yokiman; Nanchy Lepong Bulan (SEKOLAH TINGGI TEOLOGI KIBAID, 2021)
The problem of delinquency is a social problem thet can ruin public relationships and unsavory attitudes. The purpose of this study is: to learn how the church plays a role in overcoming Christian delinquency on mount moriah. In this study, the authors examined the problem using qualitative methods to approach case studies to field exploration in order to gain greater knowledge in a given situation or ini a case. The authors use several sources such as, books, journals, ang media as sources of information. As for the results of the study, the authors find that the church is not yet fully responsible and properly for the young. Among the problems involted was delinquency. This has had a negative effect on the development of a youth in his youth. For this the church must take an active role in overcoming Christian delinquency. Thus the writer sees the topic of the church’s role in overcoming Christian delinquency as highly relevant and contained in a work of writing.